(untitled) (Research, Society and Development, 2024)
Parkinson’s disease has an unknown etiology and is characterized by signs and symptoms such as rigidity, akinesia, bradykinesia, tremors, postural instability, among others. The need for more effective developments in disease management encouraged the development of this project, which aims, through a literature review, to carry out a more in-depth study of Deep Brain Stimulation (DBS) and the evolution of the procedure in recent years to the treatment of Parkinson’s disease.Through this project, the disease, symptomatology, available treatments, and promising treatments that may increase the quality and life expectancy of the patient were analyzed, aiming at reducing possible sequelae and early initiation of non-pharmacological treatment. Focusing, therefore, on the most effective surgical procedure in recent years, deep brain stimulation (DBS), which has achieved better results. The methodology involved searching for systematic reviews and meta-analyses published in English and Portuguese, in the databases PubMed, LILACS, Scielo, and Google Scholar addressing the subject. Additionally, studies found in a general search in the same databases with the same keywords, but focusing on their use in titles and abstracts, were included. It is concluded that DBS is a beneficial treatment, bringing significant improvements in the quality of life of patients with Parkinson’s. However, it is used as a last resort when drug therapy becomes ineffective and starts to bring more harm than benefit to the patient.